Analysis of Product Quality, Service Quality, Store Atmosphere, and Brand Image on Purchase Interest at the Lena Editing Art Sei Sentosa Shop - Mariska, Heni; Harahap, Nova Jayanti; Halim, Abd. (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the implications of Product Quality Analysis, Quality Service, Store Atmosphere, and Image Brand on Purchase Intention in Lena Editing Art Sei Sentosa Stores. The research method used in this research is quantitative. In this research, the population is an unknown number of consumers of the Lena Editing Art Sei Sentosa Shop. Research samples using incidental sampling techniques are techniques for determining samples based on chance, that is, anyone who happens to meet the researcher can be used as a sample if it is deemed that the person they meet by chance is suitable as a data source. This research uses a non-probability sampling technique because the number of members of the population is unknown, and purposive sampling is the sample determination technique. Because the exact size of the member population is not known, the sample size was calculated using the Cochran formula with a research sample of 96 people. The data collection techniques used were observation, documentation studies, and questionnaires. The analytical method for this research is multiple linear regression with the SPSS program. The research results prove that product quality has a positive and significant effect on purchase interest at the Lena Editing Art Sei Sentosa store. Service Quality has a positive and significant effect on Purchase Interest at the Lena Editing Art Sei Sentosa Store. Store Atmosphere has a positive and significant effect on Purchase Interest at the Lena Editing Art Sei Sentosa Store. Brand Image has a positive and significant effect on Purchase Interest at the Lena Editing Art Sei Sentosa Store. Product Quality, Service Quality, Store Atmosphere, and Brand Image simultaneously have a positive and significant effect on Purchase Interest at the Lena Editing Art Sei Sentosa Store. The coefficient of determination is 0.642, meaning that Purchase Interest can be explained by the variables Product Quality (X1), Service Quality (X2), Store Atmosphere (X3), and Brand Image (X4) amounting to 64.2%, while the remaining 35.8% can be explained by other variables not examined in this study.